NEGATIVE TRANSFER OF INDONESIAN COLLOCATIONS INTO ENGLISH AND IMPLICATIONS FOR TEACHING ENGLISH AS A FOREIGN LANGUAGE - Said, Mashadi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
One of the most challenging problems for EFL students is to be able to express themselves not just grammatically but also acceptably and naturally in English in appropriate contexts.  The ability to produce acceptable and natural expressions in English is closely related to the EFL students’ competence in collocation—which words go together in normal usage. The present study provides an empirical analysis on negative transfer made by Indonesian EFL students in lexical collocation and recommends practical ways to help students improve their competence in collocation.  Data for the study was collected from essays written by 40 EFL university students majoring in English in Indonesia whose native language is Indonesian. The students were asked to write a two- to three-page essay on an assigned topic. Of 445 lexical collocation errors found in the English writing, 321 (72%) were negative transfers of Indonesian lexical collocations into English. The findings suggest the necessity of direct teaching of collocations, the use of The Collins WordbanksOnline, and the need to design bilingual collocation dictionaries.Keywords: Negative Transfer, Lexical Collocation, Indonesian Collocation, Acceptable Collocation